Trypanosoma cruzi amino acid transporter TcAAAP411 mediates arginine uptake in yeasts - Carrillo, C. (2010)
Trypanosoma cruzi, the aetiological agent of Chagas' disease, is exposed to extremely different environment conditions during its life cycle, and transporters are key molecules for its adaptive regulation. Amino acids, and particularly arginine, are essential components in T. cruzi metabolism. In this work, a novel T. cruzi arginine permease was identified by screening different members of the AAAP family (amino acid/auxin permeases) in yeast complementation assays using a toxic arginine analogue. One gene candidate, TcAAAP411, was characterized as a very specific, high-affinity, l-arginine permease. This work is the first identification of the molecular components involved specifically in amino acid transport in T. cruzi and provides new insights for further validation of the TcAAAP family as functional permeases. © 2010 Federation of European Microbiological Societies.